'As easy as riding a bike': a systematic review of injuries and illness in road cycling. Issue 1 (10th December 2020) - Rooney, Dáire; Sarriegui, Inigo; Heron, Neil
Abstract : Objectives: To allow the implementation of effective injury and illness prevention programmes for road cyclists, we wanted to first identify the injury/illness burden to this group of athletes. We, therefore, undertook a systematic review of all reported injuries/illness in road cycling. Design: Systematic review. Data sources: Identification of articles was achieved through a comprehensive search of: MEDLINE, Embase, PsycINFO, Web of Science and Cochrane Library from inception until January 2020. Eligibility criteria for selecting studies: Studies reporting injuries/illness in adults participating in road cycling. Cycling commuter studies were excluded from the analysis. Method: Two review authors independently screened titles and abstracts for eligibility and trial quality. Initial search criteria returned 52 titles and abstracts to be reviewed, with 12 studies included after reviewing the full text articles. Results: The most common injuries sustained were abrasions, lacerations and haematomas accounting for 40–60% of the total injuries recorded. Fractures (6–15%) were the second most frequent type of injury. Head injuries (including concussions) accounted for 5–15% of injuries with musculotendinous injuries accounting for 2–17.5%. The upper limb was more frequently affected by injuries than the lower limb, with amateurs appearing to be at higher risk of injury/illness than professionals. Clavicle was the prevalent fracture, with patellofemoral syndrome the number one overuse diagnosis. No meta-analysis of the results was undertaken due to the inconsistent methods of reporting. Conclusion: This is the first systematic review of road cycling injuries. Injuries most often affected the upper limb, with clavicle being the most prevalent fracture and the most common overuse injury being patellofemoral syndrome.